The effects of forest therapy on public mental health and circular economy: A policy support model in Japan - Zhang, Shujian; Teng, Junfei; Zeng, Yan; Song, Honglin; Gu, Zhijun (Frontiers in Public Health, 2022)
Background Forest therapy has gained popularity in Japan and even other nations/regions due to its health benefits. In addition, forest therapy has contributed to the development of circular economy and industrial upgrading. Japanese successful practice can serve as a model for other countries in the Asia-Pacific region. To this end, the aim of this study was to determine whether forest therapy can improve the whole well-being of the participants and has a positive effect on the development of circular economy in the region. Methods Both empirical and inductive research methods were used; empirical approach was conducted to perform comparative analysis of regional data that was retrieved from the research project of Japanese Forestry Agency in 2015. Specifically, the efficacy of forest therapy on physical (blood glucose, blood pressure, body weight) and mental (sleep quality e.g.,) health outcomes among 815 participants was investigated. Regional data are from the statistics of Iiyama City from 1990 to 2005. After the concept of forest therapy became popular in the late 1990s, this element had a great positive impact on the economic benefits of Ishiyama City and other major forest scenic areas. We summarize and analyze a series of policies made by relevant departments of the Japanese government in the years from 2019 to 2021 to promote forest therapy and related circular industry development. Results Significant (pre-to-post participation) changes in physical measure was observed. Firstly, mean weight of those overweight participants decreased across three different time points (pre-test/enrollment = 79.7 kg, 3-month participation = 77.2, and 6-month participation = 76.8 kg), while overall mean weight of the participants decreased to 61, 60.5, and 60.4 kg, respectively. Secondly, Participant with normal weight showed a decrease on mean HbA1C (from 6.09 to 6.06) at Week 24, while overweight participants demonstrated a slight change 6.03–6.01 after 6 months the average HOMA-IR for overweight participants decreased from 3.5 to 2.5 at Week 24, while participants with normal weight demonstrated a decrease from 2.2 to 1.7 at Week 24. Forest Therapy has emerged in Japan since Mid-1990s and has attracted a large number of tourists all over the world due to its unique health benefits. Conclusion Forest therapy in Japan has positive effects on whole well-being of Japanese residents and it has helped public mental health promotion and economic growth. Under the guidance and support of government policies, it can promote the development of circular economy and industrial transformation and set a model of Japanese forest therapy development for other countries in the Asia-Pacific region.